Redemption and reproach: Religion and carceral control in action among women in prison - Ellis, Rachel (Criminology, 2020)
Criminologists are increasingly interested in how a variety of justice-adjacent institutions scaffold surveillance and punishment in the U.S. criminal justice system. A relevant but understudied institution within the carceral state is that of religion. Drawing on 12 months of ethnographic fieldwork inside a U.S. state women's prison, I interrogate how religion—predominately conservative and evangelical Protestantism—served dual purposes in light of carceral control. Religion offered redemptive narratives to counter punitive carceral narratives promulgated by the state. At the same time, this narrative shift from “flawed” to “faithful” prescribed particular forms of embodiment: avoiding fights and rejecting sexual relationships with women. These forms of Protestant embodiment aligned with carceral purposes, such that women who reprimanded others for breaching religious norms were simultaneously enforcing prison rules. Although rhetorically challenging official prison narratives on the meaning of incarceration, Protestant narratives in practice regulated women's emotional and sexual behaviors and fostered a system of informal surveillance among incarcerated women. These findings illuminate how organizational narratives are linked to individual action. More broadly, they suggest how an institution such as religion can undergird state authority within an intractable context of carceral control.